LEGALITAS PERKAWINAN DENGAN WALI HAKIM MENURUT PERATURAN MENTERI AGAMA NOMOR 30 TAHUN 2005: Marriage Legality under Minister of Religious Affairs Regulation No. 30 of 2005 regarding Magistrate Guardian - Hakim, Abdul (Faculty of Sharia and Law, Sunan Gunung Djati Islamic State University of Bandung, 2017)
AbstractOne of the legal requirements for marriage is the existence of marriage legal guardian (wali). If the legal guardian cannot act for certain reasons, the position of the guardian is transferred to a magistrate guardian (wali hakim). The magistrate guardian is discussed in various fuqaha jurisprudence and fiqh books. In Indonesia, these opinions were then uniformed through Minister of Religion Regulation Number 30 of 2005 concerning Magistrate Guardian. The applied method in this study is descriptive analysis, by describing the opinions of jurists in various fiqh books and their transformation to uniform provisions in the Minister of Religion Regulation Number 30 of 2005 concerning magistrate guardian. Sources based on the Islamic juristsâ€™s opinions include BidÄyat al-Mujtahid wa NihÄyat al-Muqtashid, Fiqh al-Sunnah, Al-Muwatha, Fath al-Muâ€˜Ä«n and Fath al-Wahab. This study shows that the most visible transformation is President as wilayah ammah, the general ruler of the country, and gives power to the Ministry of Religious Affairs to appoint the Head of Religious Affairs Distric Office to become a magistrate guardian in their respective region.Keywords:Â Â Marriage guardian, wali aqrab, magistrate guardianAbstrakSalah satu syarat sahnya perkawinan adalah adanya wali nikah. Apabila wali nikah tidak dapat bertindak atau karena sebab-sebab tertentu maka kedudukan wali nikah berÂpindah kepada wali hakim. Bertindaknya wali hakim sebagai wali nikah terdapat dalam berbagai pendapat fuqaha dalam kitab fiqh yang beragam. Di Indonesia pendapat tersebut kemudian diseragamkan melalui Peraturan Menteri Agama Nomor 30 Tahun 2005 tentang Wali Hakim. Metode yang digunakan dalam penelitian ini adalah deskriptif analitis, dengan menggambarkan pendapat fuqaha dalam kitab fiqh yang beragam sehingga menjadi ketentuan yang seragam dalam Peraturan Menteri Agama tersebut. Sumber yang berdasarkan pendapat fuqaha dalam kitab fiqih diantaranya ialah BidÄyat al-Mujtahid wa NihÄyat al-Muqtashid, Fiqh al-Sunnah, Al-Muwatha, Fath al-Muâ€˜Ä«n dan Fath al-Wahab. Penelitian ini menunjukkan bahwa transformasi paling kental adalah ketentuan mengenai presiden sebagai wilayah ammah yang memberikan kuasa kepada Menteri Agama untuk menunjuk kepala Kantor Urusan Agama Kecamatan sebagai wali hakim di wilayahnya masing-masing.Kata Kunci :Â Â Wali nikah, wali aqrab, peraturan menteri agama, wali hakimÂ